2012
DOI: 10.1136/annrheumdis-2011-201180
|View full text |Cite
|
Sign up to set email alerts
|

The impact of endogenous annexin A1 on glucocorticoid control of inflammatory arthritis

Abstract: ObjectivesTo establish the role and effect of glucocorticoids and the endogenous annexin A1 (AnxA1) pathway in inflammatory arthritis.MethodsAnkle joint mRNA and protein expression of AnxA1 and its receptors were analysed in naive and arthritic mice by real-time PCR and immunohistochemistry. Inflammatory arthritis was induced with the K/BxN arthritogenic serum in AnxA1+/+ and AnxA1−/− mice; in some experiments, animals were treated with dexamethasone (Dex) or with human recombinant AnxA1 or a protease-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 62 publications
4
46
1
2
Order By: Relevance
“…These findings are at odds with those of a recent study in which increased arthritis severity in AnxA1 −/− mice was not observed in this model (Patel et al, 2012), although these authors did observe reduced efficacy of the glucocorticoid dexamethasone in the absence of AnxA1. In that study, arthritis was induced with a higher dose of K/BxN serum than that used in the current study.…”
Section: Figurecontrasting
confidence: 57%
See 1 more Smart Citation
“…These findings are at odds with those of a recent study in which increased arthritis severity in AnxA1 −/− mice was not observed in this model (Patel et al, 2012), although these authors did observe reduced efficacy of the glucocorticoid dexamethasone in the absence of AnxA1. In that study, arthritis was induced with a higher dose of K/BxN serum than that used in the current study.…”
Section: Figurecontrasting
confidence: 57%
“…AnxA1 has been shown to ameliorate disease in several animal models of inflammation, including arthritis (Yang et al, 1999;2013b;Patel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although the anti-inflammatory activities of AnxA1 and its mimetic peptides, including Ac2-26, have been explored in several in vivo and in vitro investigations (16,(18)(19)(20)26), the role of exogenous AnxA1 in ocular inflammatory processes has not been elucidated, and there are no studies on the administration of Ac2-26 in ocular tissues. Given the common side effects of the current therapies used to treat uveitis (4,5,15), we evaluated the effects of endogenous and exogenous AnxA1 protein in rodent ocular tissues in EIU and an in vitro LPS-inflamed RPE human cell system and further evaluated AnxA1's mechanism of action.…”
mentioning
confidence: 99%
“…In monocytes and macrophages they inhibit production of proinflammatory cytokines as the result of an interaction between GC receptor monomers and proinflammatory transcription factors, such as NF-kB or AP-1, in a process called "transrepression" (4,5). GCs also induce anti-inflammatory mediators in monocytes/macrophages (e.g., annexin A1) (6,7).…”
mentioning
confidence: 99%